Family policy matters : how policymaking affects families and what professionals can do - Bogenschneider, Karen (New York Routledge, 2024)
"This new edition captures the evolving, post-pandemic landscape of family policy-the transformational changes that have occurred within contemporary families and the social, economic, and racial/ethnic disparities that have grown across families. The book draws on policies from around the globe to make an evidence-based case for family policy and its contributions to families and to society. Bogenschneider tackles a significant challenge of our times-the polarization of politics-including why it occurs and how professionals can bridge the divide"--
"First edition published by Routledge 2002"--Title page verso.
Keywords: Family policy